Genome-Wide Association Study for Test-Day Milk Yield, Proteins, and Composition Traits of Crossbred Dairy Cattle in Ethiopia - B. Rekik; T. Mestawet; A. Girma; M. Seid; J. Besufekad; S. Meseret (International Journal of Genomics)
Identifying genetic regions and candidate genes that influence milk production traits is critical for understanding genetic inheritance and improving both the quality and quantity of milk in dairy cattle. Crossbred dairy cattle significantly contribute to increasing milk production and ensuring food security in the middle- and high-altitude regions of Ethiopia. However, the genetic architecture underlying their milk yield and composition traits has not yet been thoroughly investigated. This study conducted a genome-wide association study (GWAS) on 308 crossbred dairy cows from central, northeastern, and southern Ethiopia to identify genetic markers associated with key milk production traits. Using high-density SNP chip data and the fixed and random model circulating probability unification (Farm CPU) method via the Memory-efficient, Visualization-enhanced, and Parallel-accelerated R package (rMVP) (Version 1.0.7.), we analyzed traits including test-day milk yield (TDMY), total protein (TP), casein (CN), whey (W), protein percentage (P), fat percentage (F), lactose percentage (L), total solids (TS), density (D), solids-not-fat (SNF), salt (S), and freezing point (FP). This study identified 16 significant SNPs associated with these traits, including rs41661899 on Chromosome 6, which was significantly associated with both TP and W, and rs42274954 on Chromosome 12, which was significantly associated with CN. Eight SNPs, such as rs43560693, rs109098713, rs111029661, rs134499665, rs133908307, rs133627532, rs42098411, and rs110066280, were found across multiple chromosomes (8, 10, 14, 15, 19, 21, 26, and 28, respectively) and were significantly associated with milk P. Additionally, SNPs rs110844447 and rs135995768 on Chromosomes 6 and 14 were significantly associated with D and FP, respectively. Three SNPs, including rs109564259, rs135552551, and rs41620904 on Chromosomes 6, 11, and 24, were significant associations with S. Candidate genes identified near and within these SNPs include TRAM1L1, DIAPH3, PEBP4, WDR89, BCAS3, RALGAPA1, HABP2, NRG3, HPSE, PCDH7, LINC02579, TRNAS-GGA, and OR5CN1P. These findings enhance our understanding of the genetic architecture of milk-related traits in Ethiopian dairy cattle and highlight the potential for marker-assisted selection to improve milk production and composition in breeding programs.